The cultural life of money - Gil, Isabel Capeloa; Silva, M. Helena Gonçalves da (Culture & conflict, 2015)
The book discusses how culture simultaneously shapes and is shaped by the economy. Over the past few years, as the world has staggered from one financial crisis to another, the neat separation of economics and culture has constantly been challenged. This collection analyzes the process whereby a material icon invested with the symbolical power to rule social exchange becomes an explanatory narrative determining the way societies produce meaning